Exploring the Impact of AI Integration in Educational Practices on Teacher perceived Self-efficacy - Benchine,Ayat; BOUMEDIENE, Houda (Faculty of Letters and Foreign Languages Department of English, 2025)
Artificial Intelligence (AI) has gained increased attention recently , it has the potential to revolutionize various aspects modern life, including education and English language teaching. It has significantly influenced both students and teachers, especially when it comes to their confidence. This research aimed to examine how integrating AI technologies impact teachers’ confidence and self-efficacy. The research employed mixed method approach combining quantitative and qualitative data, to explore EFL teachers’ use of AI, and their attitudes towards its effectiveness in ELT. It also investigates the main institutional and individual factors that influence teachers’ readiness to adopt AI in ELT setting. The findings of this study highlighted positive perceptions of AI’s pedagogical value, which are significantly associated with increased integration of AI tools in classroom, presenting AI tools as an effective and powerful tool in academia and EFL context. Moreover, the results indicated a significant positive correlation between EFL teachers’ self-efficacy and their likelihood of adopting AI technologies ; teachers with high self-efficacy display high levels of willingness to integrate AI tools in their teaching practices. Furthermore, EFL teachers demonstrated that access to formal training can significantly enhance teachers’ readiness to adopt AI in classrooms. Thus, further studies are recommended including examining the correlation between AI use and students’ self-efficacy to explore the influence of AI technologies in students’ confidence and self-efficacy, another recommended are of research is the relationship between AI use in educational practices and teachers’ knowledge and teaching experience. Exploring this connection would provide valuable insights on how AI influences professional development, pedagogical strategies, and classroom effectiveness